PPH Butterfly: a novel device to treat postpartum haemorrhage through uterine compression. Issue 1 (2nd January 2017) - Cunningham, Caroline; Watt, Peter; Aflaifel, Nasreen; Collins, Simon; Lambert, Dot; Porter, John; Lavender, Tina; Fisher, Tony; Weeks, Andrew
Abstract : Objective: Postpartum haemorrhage (PPH) is a significant cause of maternal morbidity and mortality. The most common cause is an inability of the uterus to contract adequately after childbirth. In bimanual compression (BMC), one hand is placed within the vagina and the other hand is on the abdominal wall to compress the uterus. It is effective, but very uncomfortable for the woman. We designed a device that could replicate BMC without inserting a hand vaginally, therefore being less invasive. It could also help in diagnosing the source of the bleeding. Design: Mixed methods, combining an iterative design process with input from clinicians in simulations, and focus groups of clinicians and consumers. Setting: Department of Women's and Children's Health and Department of Medical Physics and Clinical Engineering, University of Liverpool, UK. Methods: A multidisciplinary team developed the design, using an obstetric manikin. Clinician and consumer groups also gave input on the concept and design. A healthcare product company and prototype manufacturer provided input into strategy, design and manufacture. Results: The PPH Butterfly is a single piece, plastic medical device that replicates BMC. It is designed to be easy to use and low-cost and allows for smooth insertion and removal. It is acceptable to clinicians and consumers and performs well in tests. Conclusions: This is the first device designed to replicate BMC while being less invasive. It could potentially be an effective form of PPH management, while also diagnosing the source of the bleeding. The device will now be tested in humans.